CORRELATION OF N-TERMINAL PRO-BRAIN NATRIURETIC PEPTIDE (NT PRO BNP) WITH SERUM FERRITIN AND NUMBER OF BLOOD TRANSFUSIONS IN THALASSEMIA PATIENTS-A CROSS-SECTIONAL STUDY - DUTT, APARNA; KARIYAPPA, MALLESH; RANGEGOWDA, RAVICHANDRA KOTHUR (International Journal of Current Pharmaceutical Research, 2023)
Objective: Thalassemia is a genetic disorder of globin chain production in which there is an imbalance between alpha globin and beta globin chain production. Thalassemia patients require frequent blood transfusions to maintain adequate tissue oxygenation, which can cause a state of iron overload. NT pro BNP is a sensitive biomarker to detect cardiac iron overload. Our objective of this study was to estimate the level of NTproBNP in beta-thalassemia patients and to find out the correlation of NT pro BNP with serum ferritin levels and the number of blood transfusions. Methods: 50 thalassemic patients aged below 18 y with no known cardiac comorbidities were enrolled in this cross-sectional study. The correlation between the levels of NT-pro BNP with serum ferritin and number of blood transfusions and chelation therapy was measured. Results: This study demonstrated that the levels of NT Pro BNP were elevated in thalassemia patients with a positive correlation with serum ferritin values and the number of blood transfusions which the patients received. Conclusion: This Study also concluded that NT Pro BNP can be used as a biochemical marker used to detect early stages of cardiac failure and also to identify patients going for heart failure, especially in resource-limited settings.